Innovations for diagnostics and treatment of injuries and disorders of musculoskeletal system in Irkutsk Scientific Center of Surgery and Traumatology (to the 70th anniversary of Scientific Research Institute of Traumatology and Orthopedics) - V. A. Sorokovikov (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The article summarizes experience and achievements of Irkutsk Scientific Research Institute of Traumatology and Orthopedics (now - Irkutsk Scientific Center of Surgery and Traumatology) over a 70-year period. The development of new methods of diagnostics and treatment and organization of health care for patients with traumatological and orthopedic pathology are highly influenced by the Institute. The team of Irkutsk Scientific Center of Surgery and Traumatology developed a new promising direction of combined tension-band osteosynthesis, substantiated organ-sparing endoprosthesis replacement, created new technologies of treatment of chronic osteomyelitis, developed concept of treatment of spinal trauma and spinal cord injuries, determined regularities of cross-system organization of physiological functions at the musculoskeletal system pathology, created original technologies and instruments for the treatment of musculoskeletal system traumas and disorders. Innovations created in ISCST include 330 patents. Irkutsk Scientific Center of Surgery and Traumatology was awarded Governor's Award in Science and Technics for the development and introduction in clinical medicine of new diagnostic and treatment methods and of candidate medicines in 2012 and 2013.